Strategic communication in cultural organizations, the landscape museum - Centeno, Maria João (2021)
This chapter intends to explore the role of strategic communication in cul tural organizations, presenting the Landscape Museum. Since the field of strategic communication does not have a unifying conceptual framework (Hallahan et al., 2007), this work intends to explore one of the various com munication pursuits: building and maintaining relationships or networks through dialogue. The Landscape Museum’s mission is to contribute to the development of a landscape citizenship, awakening a critical and participa tory sense in citizens. The museum has been trying to achieve it by build ing and maintaining strong and permanent relationships through dialogue. Since “strategic communication also includes examining how an organi zation presents itself in society as a social actor in the creation of public culture and in the discussion of public issues” (Hallahan et al., 2007, p. 27) and considering Self’s (2015) proposal for dialogue, it “is not just about achieving consensus, but facilitates debate and advocacy in public policy formation” (p. 74), this chapter presents how the Landscape Museum specif ically through its educational service has been promoting the acceptance, through dialogue, of ideas related to landscape’s protection and valoriza tion and thus contributing to landscape citizenship.